Health care costs associated with hepatocellular carcinoma: A population‐based study. Issue 4 (15th March 2013) - Thein, Hla‐Hla; Isaranuwatchai, Wanrudee; Campitelli, Michael A.; Feld, Jordan J.; Yoshida, Eric; Sherman, Morris; Hoch, Jeffrey S.; Peacock, Stuart; Krahn, Murray D.; Earle, Craig C.
<x xml:space="preserve">Abstract</x> Although the burden of hepatocellular carcinoma (HCC) is an escalating public health problem, it has not been rigorously estimated within a Canadian context. We conducted a population‐based study using Ontario Cancer Registry linked administrative data. The mean net costs of care due to HCC were estimated using a phase of care approach and generalized estimating equations. Using an incidence approach, the mean net costs of care were applied to survival probabilities of HCC patients to estimate 5‐year net costs of care and extrapolated to the Canadian population of newly diagnosed HCC patients in 2009. During 2002‐2008, 2, 341 HCC cases were identified in Ontario. The mean (95% confidence interval [CI]) net costs of HCC care per 30 patient‐days (2010 US dollars) were $3, 204 ($2, 863‐$3, 545) in the initial phase, $2, 055 ($1, 734‐$2, 375) in the continuing care phase, and $7, 776 ($5, 889‐$9, 663) in the terminal phase. The mean (95% CI) 5‐year net cost of care was $77, 509 ($60, 410‐$94, 607) and the 5‐year aggregate net cost of care was $106 million ($83‐$130 million) (undiscounted). The net costs of patients receiving liver transplantation only and those undergoing surgical resection only were highest in the terminal phase. The net cost of patients receiving radiofrequency ablation as the only treatment was relatively low in the initial phase, and there were no significant differences in the continuing and terminal phases. Conclusion: Our findings suggest that costs attributable to HCC are significant in Canada and expected to increase. Our findings of phase‐specific cost estimates by resource categories and type of treatment provide information for future cost‐effectiveness analysis of potential innovative interventions, resource allocation, and health care budgeting, and public health policy to improve the health of the population. (Hepatology 2013;58:1375–1384)